2018
DOI: 10.1371/journal.pone.0203849
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of dental zirconia ceramics affected by ultrasonic scaling and low-temperature degradation

Abstract: Zirconia (3Y-TZP) dental prostheses are widely used in clinical dentistry. However, the effect of ultrasonic scaling performed as a part of professional tooth cleaning on 3Y-TZP dental prostheses, especially in conjunction with low-temperature degradation (LTD), has not been fully investigated. The present study aimed to evaluate the influence of ultrasonic scaling and LTD on the surface properties of 3Y-TZP in relation to bacterial adhesion on the treated surface. 3Y-TZP specimens (4 × 4 × 2 mm) were polished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 45 publications
(51 reference statements)
2
37
1
Order By: Relevance
“…Another study examining bacterial adhesion on varied restorative materials after plaque removal via scaling both steel curette and ultrasonic scaler points to scalers did not affect zirconia surface roughness (34). In contrast to the present study, Nakazawa et al (25) reported that ultrasonic scaling increases the surface roughness with or without aging. They observed that small pits were formed on the zirconia surface instead of scratches, and they concluded that this occurred due to particle break off from the surface due to LTD. Vigolo, too, examined the effect of steel and titanium curettes on zirconia and lithium disilicate surfaces and concluded that the steel curette increased the zirconia surface roughness (35).…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Another study examining bacterial adhesion on varied restorative materials after plaque removal via scaling both steel curette and ultrasonic scaler points to scalers did not affect zirconia surface roughness (34). In contrast to the present study, Nakazawa et al (25) reported that ultrasonic scaling increases the surface roughness with or without aging. They observed that small pits were formed on the zirconia surface instead of scratches, and they concluded that this occurred due to particle break off from the surface due to LTD. Vigolo, too, examined the effect of steel and titanium curettes on zirconia and lithium disilicate surfaces and concluded that the steel curette increased the zirconia surface roughness (35).…”
Section: Discussioncontrasting
confidence: 90%
“…A previous study investigating the effect of ultrasonic scaling and LTD on phase transformation stated that ultrasonic scalers did not affect the phase transformation on the zirconia surface. But independent of the ultrasonic scaling processes, LTD increased the t→m phase transformation and decreased the material's surface hardness (25). Although our findings are partially compatible with the study mentioned above, the phase transformation percentages differed from ours due to the extended aging time for LTD. Sc and USc groups indicated lower surface hardness results, but there were no important changes in the other groups.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…After screening, 26 studies were selected for a full-text evaluation to assess their eligibility according to the selection criteria. After the evaluation, 11 studies [ 25 26 27 28 29 30 31 32 33 34 35 ] were included for the final review. Fifteen studies did not meet the inclusion criteria and were excluded for the following reasons: the study did not investigate interventions for decontamination purposes (n=9); the study did not use zirconia as an implant material (n=5); or there was no comparator or control group (n=1).…”
Section: Resultsmentioning
confidence: 99%